Job satisfaction among neonatal residents and postgraduate students at a tertiary care center in Montevideo, Uruguay - De los Santos, Jennise (2025)
This study evaluated the job satisfaction of resident physicians in the Neonatology Service of the Pereira Rossell Hospital Center in Montevideo, Uruguay. Twenty-five participants (80% women) were included, distributed across three years of training, and the expanded Font-Roja questionnaire was applied. The results show that the dimensions with the highest satisfaction were interpersonal relationships with colleagues (mean 1.6) and job satisfaction (2.1). However, critical dimensions with high levels of dissatisfaction were identified, such as job-related tension (3.7), extrinsic status characteristics (3.7), and work pressure (3.52). Analysis by year of training revealed statistically significant differences in job satisfaction (p = 0.04952) and extrinsic characteristics (p = 0.03205), while no significant differences were observed between age groups (<30 years and ≥30 years). These findings underscore the influence of extrinsic and intrinsic factors on job satisfaction, highlighting the need for specific interventions to improve working conditions and reduce psychosocial risks, such as burnout.